Quo Vadis Glagah Village Development Innovation, Lamongan District - Alam, Bahrul; Maulana, Ilham Nur Hanifan; Nashihah, Durratun (Sekolah Pascasarjana Universitas Brawijaya, 2023)
Glagah Village, Lamongan Regency, is an independent village in Indonesia. Every town in Indonesia carries out rights and obligations by Law Number 6 of 2014 concerning villages. Implementation of Village Administration, Implementation of Village Development, Development of Village Communities, and Empowerment of Village Communities. This study aims to describe the typology of innovation from Quo Vadis Village Development Innovation in Glagah Village and to find out the supporting and inhibiting factors that are carried out to be able to optimize village development in the process of innovation and development so that village development can make an innovation in improving the quality of development and being an appropriate target because the innovation process is the initial planning in the implementation of village development. The research method used in this research is descriptive research with a qualitative approach. The study results show that Glagah Village has carried out Quo Vadis village development innovations, which are carried out in stages, from the hamlet meeting to the village meeting forum stage. Keywords: innovation, village development, government village, infrastructure development